2016
DOI: 10.1007/s10615-016-0606-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Experiences of an Attachment-Based Intervention for Parents Troubled by Intimate Partner Violence

Abstract: It is known that intimate partner violence (IPV) negatively affects both parental capacity and children’s well-being, but few studies have focused on the experiences of those taking part in family interventions focused on IPV. In this study, 26 parents (16 mothers and 10 fathers) with a history of IPV participated in focus groups concerning their attachment-based group intervention experience in the program Parenting and Violence. The transcripts, subjected to thematic analysis, showed that participants experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Earlier studies also demonstrated the efficacy of attachment-based intervention models (i.e. Allen et al 2014 ; Crugnola et al 2016 ; Kamal et al 2016 ; Moretti et al 2015 ; Shpigel et al 2012 ; Zilberstein and Messer 2010 ) but possessed limitations that reduced their usefulness in medical conditions. These attachment-based intervention models were done with families, couples or individuals of different ages and from different situations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies also demonstrated the efficacy of attachment-based intervention models (i.e. Allen et al 2014 ; Crugnola et al 2016 ; Kamal et al 2016 ; Moretti et al 2015 ; Shpigel et al 2012 ; Zilberstein and Messer 2010 ) but possessed limitations that reduced their usefulness in medical conditions. These attachment-based intervention models were done with families, couples or individuals of different ages and from different situations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions targeting parenting should be responsive to gender, dimensions of IPV, and the context of familial 972 Journal of relationships (Lindhorst & Tajima, 2008). This includes accounting for the unequal burden of caring that is most often placed on mothers (Kamal et al, 2017).…”
Section: Gender Differences In Patterns Of Ipvmentioning
confidence: 99%
“…Participants were offered the opportunity to have their journals returned to them at the conclusion of data analysis. Kamal et al (2017) identify focus groups as an appropriate method to gain an understanding of participant perspectives surrounding parenting programs. Thus, a focus group was held with all participants in the community attachment parenting program.…”
Section: Data Collectionmentioning
confidence: 99%